Revisiting Scalable Coherent Shared Memory. - Bell, C. Gordon; Nassi, Ike (Computer (00189162), 2018)
Scalable and coherent shared memory has been a long-sought-after but elusive goal. In contrast to today’s popular distributed-computing models, the authors present a software-defined server architecture that is a scale-up shared-memory multiprocessor, yet uses ubiquitous commodity scale-out clusters.